Influence of College Student’ Artificial Intelligence Quotient on Employability - Cheng, Xingjing; Cai, Yuanfeng (Journal of Roi Kaensarn Academi, 2024)
This study establishes on the review of relevant Chinese and foreign literature and the interview results, three variables of college students' employability, artificial intelligence quotient and self-regulation index system are established, and reliability analysis, exploratory factor analysis and confirmatory factor analysis are carried out. Secondly, AMOS22.0 is used to build a structural equation model to analyze the effects of artificial intelligence quotient and self-regulating variables on college students' employability. SPSS22.0 was used to explore the influence of artificial intelligence quotient and self-regulation on college students' employability, and the adjustment effect of self-regulation variables was analyzed. The results show that the creativity, data power, communication power, learning power and individual acceptance of college students will positively and significantly affect their employability in the intelligent era. College students' artificial intelligence quotient and self-regulation will positively and significantly affect their employability. Self-regulation can significantly enhance the influence of artificial intelligence quotient on the employability of college students, that is, self-regulation has a significant positive regulating effect on the influence path of artificial intelligence quotient on the employability of college students.